1996
DOI: 10.3171/jns.1996.84.5.0818
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after operation for trigeminal neuralgia in patients with posterior fossa tumors

Abstract: During a 20-year period, 26 patients with typical symptoms of trigeminal neuralgia were found to have posterior fossa tumors at operation. These cases included 14 meningiomas, eight acoustic neurinomas, two epidermoid tumors, one angiolipoma, and one ependymoma. The median patient age was 60 years and 69% of the patients were women. Sixty-five percent of the symptoms were left sided. The median preoperative duration of symptoms was 5 years. The distribution of pain among the three divisions of the trigeminal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 64 publications
4
67
0
3
Order By: Relevance
“…The mechanism of pain production by intracranial tumors was considered to be a direct trigeminal root compression or vascular compression secondary to displacement by the tumor [5,9]. As mentioned above, one patient with a vestibular schwannoma complained of continued facial pain despite the decrease in tumor volume, and follow-up MRI revealed vascular compression which had not been identified at prior imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of pain production by intracranial tumors was considered to be a direct trigeminal root compression or vascular compression secondary to displacement by the tumor [5,9]. As mentioned above, one patient with a vestibular schwannoma complained of continued facial pain despite the decrease in tumor volume, and follow-up MRI revealed vascular compression which had not been identified at prior imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al [8] also reported good results of radiosurgical treatment of tumor-related trigeminal neuralgia. They reported favorable results (pain relief more than 50% in 88.9% of cases) corresponding to the results of microsurgical resection of tumors [5]. However, these two radiosurgical reports have the limitation of a short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В тех случаях, ко-гда клиника классической НТН сопровождается чувствительным дефицитом, используют термин чувствительная тригеминальная нейропатия [331,423]. У больных рассеянным склерозом также наблюдается НТН, которую многие авторы относят ко вторичной НТН [63,74,154,158,169,170,184,340,354,365,366,378].…”
Section: от истоков к современному взгляду на патогенезunclassified
“…2,3 We report a case of trigeminal neuralgia caused by an artery that had almost encircled the nerve, which was successfully decompressed surgically, and discuss the anatomy of the offending artery and trigeminal nerve root vasculature. …”
mentioning
confidence: 99%